Ovipositional behaviour of two mango fruit fly species (Diptera Tephritidae) in relation to Oecophylla cues (Hymenoptera Formicidae) as compared to natural conditions without ant cues - Vayssières, Jean-François; Sinzogan, A.A.C.; Adandonon, A.; Mele, P. van; Korie, S. (2013)
The tritrophic interactions between mangoes (Mangifera indica), two frugivorous fly species of greateconomic significance, Bactrocera invadens and Ceratitis cosyra, and weaver ants (Oecophylla longinoda)were studied in Benin. We investigated whether Oecophylla cues affect B. invadens and C. cosyra ovipositionbehaviour compared to natural conditions. Results show that on un-marked fruits, both C. cosyra and B.invadens adults have different active periods and length of oviposition, both under laboratory and fieldconditions. Compared to their landing on unmarked fruits at 7h after confinement, 46% of B. invadensrefrained from landing on fruits marked with Oecophylla cues, while C. cosyra reduced its landing by 73%. Incontrast to the un-marked fruit, both tephritid species significantly reduce oviposition duration and ovipositedless in fruits when weaver ants had patrolled on them before. Moreover, no significant difference was detectedbetween C. cosyra and B. invadens, in number of pupae produced, when confined with ant-marked fruits.Ecological and behavioural implications of our observations are discussed.